(3VhA GdeUHGM aj Yde GdeYGfi hGdHjGf hGdHOjYs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s ((3EHQGgje Hf Ydi GdSYOi GdePMLi GdRjOi s)
(3ChdgG (B:s
(3GdHdGZI EUWdGMkG (B: (3GdHdhZ ai UhZ GdcdGe EdG MO dg JhajI HJeGe GdeQGO s
(3BNQgG (B:s
(3hGdSfGO GdMQai , aPcQJ JJejekG ddaGFOI Je GdeNJUQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQgG eYGQVI SfI (B877(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO Hf Ydi GdeLGgO GdNGUI HJYR s
Keywords: (3GddZIs